Detailed flow measurement of the field around tidal turbines with and without biomimetic leading-edge tubercles. (October 2017) - Shi, Weichao; Atlar, Mehmet; Norman, Rosemary
Abstract: This paper focuses on implementing detailed flow measurement using advanced Particle Image Velocimetry (PIV) system to investigate the flow mechanism of leading-edge tubercles on tidal turbine blades. Two approaches have been applied: one is 2D PIV to map the flow separation around the blade sections at different radial positions; and the other is Stereo PIV to conduct a volumetric measurement in the wake field to reveal the tip vortex development and also velocity distribution. The research presented in this paper further demonstrates that the leading-edge tubercles can enable the flow to remain attached to the blades and weaken the three dimensional effect which can lead to efficiency loss or the so-called "tip loss". Based on these phenomena that have been observed and concluded from the tests, the mechanism by which leading-edge tubercles can provide additional torque and thrust for a tidal turbine has been explained within this paper. Highlights: Biomimetic concept of applying leading-edge tubercles on a tidal turbine blade has been performed. 2D PIV and Stereo PIV have been conducted on a set of tidal turbines. Performance improvement by leading-edge tubercles has been confirmed with flow measurement result. The leading-edge tubercles can enable the flow to remain attached to the blades and weaken the three dimensional effect.